Material world : the intersection of art, science, and nature in ancient literature and its Renaissance reception - Hedreen, Guy Michael, 1958- (NIKI studies in Netherlandish-Italian art history ;, 2021)
"The interplay between nature, science, and art in antiquity and the early modern period differs significantly from late modern expectations. In this book scholars from ancient studies as well as early modern studies, art history, literary criticism, philosophy, and the history of science, explore that interplay in several influential ancient texts and their reception in the Renaissance. The Natural History of Pliny, De Architectura of Vitruvius, De Rerum Natura of Lucretius, Automata of Hero, and Timaios of Plato among other texts reveal how fields of inquiry now considered distinct were originally understood as closely interrelated. In our choice of texts, we focus on materialistic theories of nature, knowledge, and art that remain underappreciated in ancient and early modern studies even today"--